Diurnal variations of the optical properties of phytoplankton in a laboratory experiment and their implication for using inherent optical properties to measure biomass - Poulin, C.; Antoine, David; Huot, Yannick (Optical Society of America, 2018)
© 2018 Optical Society of America Diurnal variations of phytoplankton size distributions, chlorophyll, carbon and nitrogen content, in vivo fluorescence and associated optical absorption and scattering properties were observed in the laboratory to help understand in situ and spatial observations. We grew triplicate semi-continuous cultures of T. pseudonana, D. tertiolecta, P. tricornutum and E. huxleyi under a sinusoidal light regime. We observed diurnal variations in the particulate absorption (ap), scattering (bp), attenuation (cp), and backscattering coefficients (bbp), which correlate with carbon and Chl concentrations. Relative variations from sunrise of bbp are slightly lower than those of cp, suggesting that bbp diurnal increases observed in nature are partly caused by phytoplankton. Non-concurrent changes of carbon and Chl-specific backscattering and scattering coefficients and optical cross-sections however indicates that using backscattering to infer scattering or biomass must be done with care.